Effects of Irisin on Ghrelin Levels in High-Fat Diet-Induced Obese Female Rats - Bilgin, Batuhan; Hekim, Munevver Gizem; Bulut, Ferah; Kelestemur, Mirac; Ulker, Nazife (Karger, 2021)
[Abstract Not Available]
Keywords: Irisin; ghrelin; obesity; female rat